Chapter Cultural and sensorial correlates of Trebbiano wine consumption - Fabbris, Luigi (Proceedings e report, 2023)
In this paper we highlight the sensorial and cultural correlates of the consumption of Trebbiano wine produced in the Abruzzo region, Italy. The data have been collected through a questionnaire survey on a sample of 48 adults. The sample was conveniently selected among the participants at a scientific meeting held in Pescara in September 2018. The survey was part of a complex sensorial experiment concerning the preference of this white wine with respect to a series of other regional white wines. The collected data on Trebbiano wine consumption have been analysed through a path analytic regression model in which consumption was the criterion variable, while cultural and sensorial variables, on the one hand, and wine expertise and drinking habits, on the other, were the variables mediating the respondents' disposition towards this type of wine. The analysis showed that two thirds of the respondents frequently or occasionally used to consume the topical wine. The frequency of consumption was strictly influenced by the relevance the respondents conferred to this wine when put in competition with other wines during an outdoor dinner. The consumers who particularly appreciated it were wine experts (sommeliers, wine course attendants, wine producers) and other wine consumers able to recognise the intrinsic characteristics of a wine thanks to the sensorial skills (for smell and aroma evaluation) they developed through long experience and specific learning.